2017
DOI: 10.1016/j.jvoice.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Voice Problems and Noise Reports Between Teachers of Public and Private Schools in Upper Egypt

Abstract: The working conditions and vocal health of teachers in Upper Egypt, especially in public schools, are alarming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Another key finding of this study revealed that there were more teachers in the VDI > 7 group who reported using “very loud” and “excessively loud” voice in class and fewer subjects who stated to use “not at all loud” and “slightly loud” voice compared to the VDI ≤ 7 group. Similarly, Bolbol, Zalat, Hammam, and Elnakeb [ 8 ] identified that high voice loudness is a significant voice disorder risk factor that affects elementary, middle, and high school teachers’ voice in Egypt. Sathyanarayan, Boominathan and Nallamuthu [ 24 ] found that speaking in an uncomfortable loud voice was identified as one of the vocal abuse or misuse behaviors frequently used by teachers in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another key finding of this study revealed that there were more teachers in the VDI > 7 group who reported using “very loud” and “excessively loud” voice in class and fewer subjects who stated to use “not at all loud” and “slightly loud” voice compared to the VDI ≤ 7 group. Similarly, Bolbol, Zalat, Hammam, and Elnakeb [ 8 ] identified that high voice loudness is a significant voice disorder risk factor that affects elementary, middle, and high school teachers’ voice in Egypt. Sathyanarayan, Boominathan and Nallamuthu [ 24 ] found that speaking in an uncomfortable loud voice was identified as one of the vocal abuse or misuse behaviors frequently used by teachers in India.…”
Section: Discussionmentioning
confidence: 99%
“…Significant identified factors were: the number of years of teaching, high background noise levels while teaching, psychological stress while teaching, improper breath management (holding breath while speaking), upper respiratory tract infections, thyroid problems, and acid reflux. Bolbol et al [ 8 ] studied risk factors for voice disorders among Egyptian school teachers. Significant risk factors pinpointed were the number of years of teaching (15 or more years of teaching) and the number of classes per week (15 or more classes per week).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The intense noise most of the time forces them to raise the voice to communicate, potentially causing important changes, such as dysphonia 29,30 . The inadequate temperature and the dust present in the room are factors that bother the professors; these circumstances have been investigated by speechlanguage-hearing pathologists for some time 20,31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that, 48% reported moderate or severe dysphonia (speaking difficulty) within the last 6 months. Frequent feelings of being in noise were reported by all the teachers and 82% of them felt it mostly during the working day, which made them to raise their voice (Abo-Hasseba et al 2016). This suggests that poor thermal performance and acoustics could cause health problems in schools.…”
Section: Temperature and Acousticsmentioning
confidence: 99%